Comparing REM- and NREM-Related Obstructive Sleep Apnea in Jordan: A Cross-Sectional Study - K. Al Oweidat; S. A. AlRyalat; M. Al-Essa; N. Obeidat (Canadian Respiratory Journal)
Obstructive sleep apnea (OSA) is a common disorder that includes an intermittent mechanical obstruction of the upper airway during sleep, which can occur either during rapid eye movement (REM) phase or non-REM (NREM) phase. In this study, we aim to evaluate the differences in demographic and polysomnographic features between REM- and NREM-related OSA in a Jordanian sample, using both the broad and the restricted definitions of REM-related OSA. All patients who were referred due to clinical suspicion of OSA and underwent sleep study were screened. We included patients with a diagnosis of OSA who had Apnea-Hypopnea Index (AHI) greater than or equal to five. We classified patients into REM-related OSA according to either the broad definition (AHIREM/AHINREM ≥ 2) or the strict definition (AHIREM > 5 and AHINREM < 5 with a total REM sleep duration of at least 30 minutes), and patients with AHIREM/AHINREM less than two were classified as NREM-related OSA. A total of 478 patients were included in this study with a mean age of 55.3 years (±12.6). According to the broad definition of REM-related OSA, 86 (18%) of OSA patients were classified as having REM-related OSA compared to only 13 (2.7%) patients according to the strict definition. Significant differences were found between both NREM-related OSA and REM-related OSA according to the broad and to the strict definitions for arousal index (p<0.001 and p<0.032), respectively, duration of saturation below 90% (p<0.001 for both), and saturation nadir (p<0.036 and p<0.013), respectively. No significant differences were found between this group and other OSA patients regarding age, BMI, ESS, and snoring. Our study showed that the stricter the definition for REM-related OSA, the milder the associated clinical changes.